ANALISIS PENGARUH BRAND IMAGE (CITRA MEREK), KUALITAS PRODUK, DAN HARGA TERHADAP MINAT BELI PRODUK MIE INSTAN SUPERMI ( Studi Kasus Pada Konsumen Mie Instan Supermie di Kota Semarang ) - Oktaviani, Lusia; Sutopo, Sutopo (Faculty of Economics and Business Diponegoro University, 2014)
This study aims to examine how much influence of the product Brand Image, Product Quality, and Product Purchase Price enable the company to find out main factors of consumer behaviors attitudes of a product. Mostly it is applied in the food industry wherein instant noodles have become staple demands for consumers.Â Â Â Â Â Â Â Â Â Â Â This research was conducted using questionnaires distribution survey method an purposive sampling of some noodles with brand â€œ Supermiâ€ to consumers,and was analyzed by multiple linear regression. This model emphasizes the influence of product Brand Image, Product Quality, and Product Purchase Price which the final analysis result was well done by using SPSS 22.Â Â Â Â Â Â Â Â Â Â Â Research shows, three hypotheses which have been tested in this study such as Product Brand Image, Product Quality, and Product Purchase Price, have significant positive effects on consumer behaviors attitudes towards instan noodles â€œSupermiâ€ especially in Semarang. The result has showed and confirmed that this kind of research model is acceptable.